Graphene-based biosensors for disease theranostics: Development, applications, and recent advancements - Alhazmi Hassan A.; Ahsan Waquar; Mangla Bharti; Javed Shamama; Hassan Mohd. Zaheen; Asmari Mufarreh; Al Bratty Mohammed; Najmi Asim (Nanotechnology Reviews, 2021)
Graphene, owing to its unique chemical structure and extraordinary chemical, electrical, thermal, optical, and mechanical properties, has opened up a new vista of applications, specifically as novel sensing platforms. The last decade has seen an extensive exploration of graphene and graphene-based materials either alone or modified with nanoparticles and polymers for the fabrication of nanoscale biosensors. These biosensors displayed excellent conductivity, high sensitivity, and selectivity, good accuracy, and precision, rapid detection with low detection limits as well as long-term stability. The unmatched properties of graphene and graphene-based materials have been applied for the detection of a number of chemical and biological molecules successfully for the diagnosis of a variety of diseases, pathogens, and biomarkers of the diseases. This review is aimed to cover the fabrication methods, functionalization techniques, and biomedical applications along with the recent advancements in the field of development of graphene-based biosensors. Recent clinical trials and patents as well as market trends and opportunities associated with graphene-based biosensors are also summarized. The application of graphene-based biosensors in the detection of SARS-CoV-2 causing COVID-19 is also reviewed.